IDENTIFICATION AND ENDODONTIC TREATMENT OF THREE-CANALLED MAXILLARY FIRST PREMOLAR - Agwan, Atif Saleem; Sheikh, Zeeshan (Journal of Ayub Medical College Abbottabad, 2016)
Maxillary premolars exhibit variable root canal morphology, but it is quite rare to find three canals in their root system. The aim of this case report is to present the diagnosis and clinical management of a patient with anatomical variation of having three root canals in the maxillary first premolar. Three-canalled maxillary premolars are quite an endodontic challenge. A discussion is provided here to facilitate the early recognition of these canals, access cavity modifications for better intra-canal preparation and obturation procedures. Clinicians are required to be aware of the anatomical variations they may encounter when dealing with maxillary premolars and should be trained to apply this knowledge in the clinical scenario. Keywords: Maxillary first premolar; anatomical variations; root anatomy; endodontics